In harm’s way: moral injury and the erosion of trust for emergency responders in the United Kingdom - Verity Bell; Esther Murray; Luna Muñoz; Charlotte Krahé (European Journal of Psychotraumatology, 2025)
Background: Moral injury describes the impact of witnessing or being part of events that violate one’s values. Initially described in relation to conflict and war, recent work shows that moral injury is a relevant concept for professionals working in emergency situations. Emergency responders work in contexts of human suffering and make complex decisions in time-pressured, high-stakes situations, but emergency responders’ viewpoints regarding moral injury and how strongly they align with different viewpoints is currently not well understood.Objective: We sought to investigate how moral injury is conceptualised and how emergency responders in the United Kingdom (UK) relate to experiences of moral injury.Method: In this Q-methodology (mixed-methods) study, seven experts co-created a set of 45 opinion statements (Q-set) capturing different facets of moral injury in the context of emergency responding. Subsequently, N = 21 emergency responders (police, fire service, emergency medicine, ambulance, and community first-response staff) completed an online Q-sort task, sorting statements according to how much they identified with them.Results: A by-person factor analysis yielded a three-factor solution mapping onto theoretical positions of moral injury, including loss of trust in others (Factor 1), loss of trust in oneself (Factor 2), and loss of trust in authority (Factor 3).Conclusions: Our findings support the assumption that moral injury is not a unitary concept but instead comprises different facets that people may identify with to a greater or lesser extent, depending on their role. Our results suggest differences between police vs. hospital ward workers and length of time in the profession. Future research into tailored relational and systemic interventions may be required to address the variety of experiences of moral injury in emergency responders.